Assessing Loss of Market Access : Conceptual and Operational Issues - Guscina, Anastasia (IMF Working Papers; Working Paper ;, 2017)
Loss of market access (LMA) is a central element and an exacerbator of balance of payments and fiscal crises. This paper provides an operational definition of LMA, examines the predictive power of potential LMA leading indicators, attempts to determine the likely nature (temporary versus structural) of an LMA episode, and analyzes potential implications of such an assessment on the required degree of adjustment to restore market access. Finally, it highlights the possible application of the methodological framework for identifying emerging risks to market access.